Some new type optical and the other soliton solutions of coupled nonlinear Hirota equation - Nisar, Kottakkaran Sooppy; Inan, Ibrahim E.; Yepez-Martinez, H.; İnç, Mustafa (Elsevier, 2022)
In this study, we obtained some exact traveling wave solutions of coupled nonlinear Hirota equation (CNHE) by using generalized (G'/G)-expansion method. The solutions we obtained are hyperbolic, trigonometric and expo-nential solutions. Analytical results for the obtained solutions for the CNHE have been corroborated through the Mathematica 11.2 symbolic calculation. Solutions have been illustrated in 3D graphs, and 2D plots. The present method has been used to obtain exact traveling wave solutions for several nonlinear partial differential equations.
Keywords: Coupled nonlinear Hirota equation; Generalized -expansion method; Optical solitons